STUDI EKSISTENSI WIRAUSAHA ALUMNI S-1 UNIVERSITAS SRIWIJAYA TAHUN 2013 – 2019 - Ikbal Barlian; Supriyanto Supriyanto; Deskoni Deskoni; Aniek Hidrayani (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
Growing students' interest and mindset in entrepreneurship require various appropriate steps including implementing entrepreneurship education and training as well as encouraging entrepreneurial motivation through role models that can inspire entrepreneurship. This study aims to find out 1) the efforts made by Sriwijaya University alumni in developing the businesses they started as students, and 2) the efforts to maintain the existence of the businesses they built when they became alumni. The qualitative research approach was used by interviews, observation, and questionnaires via google form. Respondents in this study amounted 32 respondents who were undergraduate alumni of Sriwijaya University from 2013-2019. Based on the research that has been done, the results show that in developing a business, alumni have had the intention, determination, interest, and experience in entrepreneurship that they have had since they were students. In addition, in maintaining the business, alumni continue to innovate related to business products, expand networks/partners, and continue to adapt to developments in information technology in expanding marketing reach.